Effectiveness Model Application Contructive Teaching Learning (CTL) Interprofesional on Education - Sapartinah, Titik (International Journal of Psychosocial Rehabilitation, 2020)
Background: The cornerstone philosophy Constructive Teaching Learning (CTL) is constructivism, which emphasizes learning philosophy that learning is not just memorize. Students must construct knowledge in their own minds. That knowledge can not be separated into facts. Fact or a separate proposition, but reflect the skills that can be applied. According to the constructivist view that the acquisition of one's experience of the process of assimilation and accommodation so that a more special experience is the knowledge embedded in the minds according to one's own schemata.Purpose: The purpose of this study is analyze the effectiveness of CTL model Midwifery Care in Pregnancy (Clinical) to increase student of Midwifery Education Interprofesional MoH Polytechnic SemarangMethods: Typestudy is a quasi-experimental design with two groups of intervention and control design. The independent variable in this research is the study variable learning model Constructive Teaching Learning (CTL) and Learning Model Perceiver Mentor (LMPM), while the dependent variable Interprofesional Midwifery students of Polytechnic Education Ministry of Health Semarang. The samples in this study were students Prodi DIII Midwifery Campus Semarang in Semarang as control and students on campus Kendal as the intervention group.Results: There are differences in effectiveness between the application of the Constructive Teaching Learning (CTL) and the application of Learning Model Perceiver Mentor (LMPM) Midwifery Care in Pregnancy (Clinical) to increase interprofessional education to the students of Department of Midwifery Poltekkes Kemenkes Semarang, where the application of CTL model has a greater influence on interprofessional education improvement compared LMPM models.Conclusion : Dimension management / conflict resolution as a result of the application of CTL model indicated by the student often consider the perspectives and opinions of others. Student often seek clarification in a respectful way when misunderstandings arise. Student often using the techniques of active listening when others speak. Student often often manage or resolve conflicts with others.